Kalender Cerita Digital Bermuatan Nilai Kearifan Lokal Sebagai Strategi Penguatan Literasi Siswa di Kelas Awal - Afryaningsih, Yunika; Setyowati, Dessy (Universitas Negeri Makassar, 2023)
Literacy practice has not yet become an ideal condition in West Kalimantan. In the cultural dimension, the habit of accessing literacy materials is the province with the 3rd lowest index score. Various studies state that literacy in the early grades will affect the success of learning in other areas of learning, even in subsequent classes. This research aims to produce a digital story calendar product containing local wisdom values that are appropriate as a strategy to strengthen literacy in the early grades. This study's method adapted Borg and Gall's research procedures. In the validation test, the percentage of media expert validators was 89%, language expert validators 88%, material expert validators 90%, and education practitioners 92.1%. In addition, limited trial results were obtained by 80% in small group trials and 85% in large group trials. These results show the percentage is in the high category. Therefore, a digital story calendar contains local wisdom Values as a Strategy for Strengthening Student Literacy in Early Grades which shows that it is suitable for use in learning.